Assessment of the antimicrobial activity of three Silene species (Caryophyllaceae) against some microorganisms - Elagaily, Miloud; A. Senussi, Najma (Scientific Journal for Faculty of Science-Sirte University, 2023)
Three Silene species (Silene gallical L., Silene succulent Forsk., and Silene apetala Willd) were tested for potential anti-microbial activity against some microorganisms (Staphylococcus aureus, Serratia marcescens, Acinetobacter boumannii, Klebsella sp., Aspergillus flavus, Aspergillus niger, Cladosporium cladosporioides, and Alternaria alternata using the well diffusion assay. Solvents used in the extraction process are ethanol, methanol and acetone. The obtained results from all plant extracts showed clear antimicrobial activity against all tested microbial species, except S. succulent extracts, which had no inhibitory activity against Klebsiella sp., A. niger and A. flavus. Moreover, the acetone extract of S. gallical and S. apetala was the most effective plant extract and showed bacteriostatic, bactericidal, fungistatic and fungicidal activities against the highly susceptible species of microbes (S. aureus, S. marcescens, C. cladosporioides, and A. alternata) with MIC ranged from 3.12 to 6.25 mg/ml, MBC and MFC of 6.25 and 12.5 mg/ml. The experiments confirmed the efficacy of selected plant extracts as natural antimicrobials and suggested that they could be used in drugs to treat infectious diseases caused by the tested microbes.